Endocapsular artificial iris implantation for iris defects: Reducing symptoms, restoring visual function and improving cosmesis. (26th April 2022) - Crawford, Alexandra Z.; Freundlich, Simone E. N.; Lim, Joevy; McGhee, Charles N. J.
Abstract: Background: To investigate repair of iris defects by endocapsular implantation of an artificial iris, in relation to visual outcomes, safety profile and patient satisfaction. Methods: Retrospective, consecutive case series from Greenlane tertiary teaching hospital and Eye Institute, Auckland, New Zealand. Medical records of patients implanted with an endocapsular artificial iris were reviewed and followed for minimum 3 months. Patient characteristics, surgical management, clinical outcomes and subjective responses were recorded. Results: Nineteen artificial irises were implanted in 18 patients. Etiologies were iris melanotic lesion excision (73.7%), trauma (10.5%), congenital aniridia (10.5%) and Urrets‐Zavalia syndrome (5.3%). During postoperative follow‐up [14.1 ± 12.4 months (range: 3 to 59 months)], best corrected visual acuity (BCVA) and intraocular pressure (IOP) did not change significantly [BCVA, 0.23 logarithm of the minimum angle of resolution (logMAR) (20/32 Snellen) preoperatively vs. 0.18 logMAR postoperatively (20/25 Snellen) (Z = −0.222, p  = 0.824); IOP, 15 mmHg preoperatively vs. 17 mmHg postoperatively (Z = 1.377, p  = 0.1447)]. Mild or self‐limiting complications included: elevated IOP (42.1%), cystoid macular oedema (15.8%); persisting postoperative uveitis (15.8%) and minor vaulting of the prosthesis (15.7%). Moderate or severe complications included significant vaulting of prosthesis requiring surgical revision (5.3%) and a single eye (5.3%) with trabeculectomy and corneal graft failure. 94.4% of patients were very satisfied with the cosmesis and would be highly likely to have the procedure again. Conclusions: This study confirms that endocapsular insertion of an artificial iris is typically associated with good functional and cosmetic results and a relatively low risk of significant complications.